Implantação das ações intersetoriais de mobilização social para o controle da dengue na Bahia - Lima, Elvira Caires de (2010)
Discussions on the health-disease process and health promotion expanded the concept of health and enabled the admission that the health sector alone could not and would not have sufficient means and resources in order to effectively solve most problems and needs of the population. Then there was the need of extrapolating the limits of the health sector and articulating the knowledge of various sectors in order to promote a better health condition for the population. Accordingly, intersectionality emerged as a new logic for guiding public policies. The object of study consisted of intersectoral actions of social mobilization for dengue control, developed by the State Committee of Social Mobilization for Dengue Prevention and Control in the State of Bahia. The general aim of this study is to analyze the process of implementation of intersectoral actions of the above referred Committee from 2008 to 2009. This is an evaluative research carried out by means of a case study. A theoretical logical model was elaborated in order to guide the construction of criteria used to estimate the degree of implementation of the intersectoral actions. The categories government capacity and governability were used to identify the constraining factors and those which facilitate the implementation of the studied intervention. The collection techniques used were semistructured interviews, observation and documentary analysis. The results showed that the intersectoral actions of social mobilization for dengue control in the State of Bahia are partially implemented in spite of the commitment and interest of the State management in establishing the control of this disease by articulating the various segments of society. It was also evidenced that Committee members presented governability over the institutions they represented. The main obstacles to the implementation of the considered intersectoral actions were the concentration of duties and responsibilities into a single sector, namely health; the non-use of planning as a working tool for the represented institutions; and, especially, the deficiency in carrying out the work process of the Committee. These results evidence that the work proposal of the Committee served as a stimulus to the intersectoral articulation at the rhetorical level, but the actual implementation of the intersectoral actions remains a challenge to be conquered.